FRI0488 CLINICAL AND LABORATORY FEATURES OF PATIENTS WITH REMITTING SERONEGATIVE SYMMETRICAL SYNOVITIS WITH PITTING EDEMA COMPARED TO PATIENTS WITH SERONEGATIVE RHEUMATOID ARTHRITIS. (2nd June 2020) - Higashida-Konishi, M.; Izumi, K.; Hama, S.; Hayashi, Y.; Okano, Y.; Oshima, H.
Abstract : Background: In the case of seronegative arthritis, it was difficult to make a differential diagnosis between remitting seronegative symmetrical synovitis with pitting edema syndrome (RS3PE) and seronegative rheumatoid arthritis (seronegative RA) because the distribution of affected joints was similar and the patients with RS3PE or seronegative RA may have edema. Objectives: To compare the clinical characteristics of RS3PE and seronegative RA Methods: We retrospectively examine consecutive patients diagnosed with RS3PE or seronegative RA in our hospital from 2007 to 2019. Patients in whom both ACPA and RF were negative were included. The patients with RS3PE met the criteria of McCarty et al.: (1) pitting edema of the dorsum of both hands and both feet, (2) sudden onset of polyarthritis, (3) seronegative for ACPA and RF. (4)no radiologically evident erosions developed. The patients with seronegative RA met the EULAR/ACR 2010 criteria. The patients who were diagnosed with RS3PE at first and then diagnosed with seronegative RA afterward were included in seronegative RA group. The first analysis was performed on the affected joints, CRP, ESR, Hb, LDH, edema, the history of malignancy 2 years before and after the diagnosis, treatment, and the history of infection requiring hospitalization after the start of treatment. The affected joints were shoulders, elbows, wrists, finger joints (the MCP, and PIP joints), hips, knees, ankles, and toe joints (the MTP and PIP joints). The secondary analysis was performed on the above evaluations with a propensity score (PS) matching for age. Results: In the first analysis, 20 patients with RS3PE and 122 patients with seronegative RA were enrolled. The mean ages (RS3PE, seronegative RA) were 81.1, 67.4 years old. Females were 60.0%, 63.1%. The mean observation period was 25.4, 63.6 months. The proportion of affected joints were shoulders (25.0%, 42.6%), elbows (10.0%, 29.5%: p=0.06), wrists (85.0%, 73.8%), finger joints (80.0%, 95.1%: p=0.01), hips (0%, 9.8%), knees (40.0%, 37.7%), ankles (65.0%, 39.3%: p=0.03) and toe joints (40.0%, 32.8%). Edema at diganosis was observed in 100%, 17.21% (p <0.0001). The mean levels of the following blood tests at diagnosis were noted: CRP, 9.0 and 4.8 mg/dL (p=0.02); ESR, 87.6 and 60.7 mm/1h (p=0.003); Hb, 10.4 and 11.8 mg/dl (p=0.001); LDH, 198.3 and 177.9 U/L (p = 0.12); MMP-3, 742.5 and 633.8 ng/mL (p = 0.14). The proportion of patients with high LDH levels (>222 U/L) was 13.6% and 9.0% (p=0.0269). The proportion of patients having the history of malignancy was 20.0%, 8.2% (p=0.10). The patient treated with prednisolone as the initial treatment was 100% and 41.0%; the mean dose was 14.3 and 9.9 mg/d. After the start of treatment, the proportion of infection requiring hospitalization was 20.0 and 3.28% (p=0.002). In the secondary analysis with PS, 17 patients with RS3PE and 17 patients with seronegative RA were enrolled. The mean ages were 80.4, 78.9 years old. Females were 52.9, 76.4%. The affected joints with difference were elbows (11.8, 35.3%: p=0.10), wrists (82.4, 100%: p=0.06), and finger joints (82.4, 100%: p=0.06). The mean levels of Hb at diagnosis was 10.4, 11.4 mg/dL (p=0.01). The proportion of patients having the history of malignancy was 23.5% and 0% (p=0.03). After the start of treatment, the proportion of infection requiring hospitalization was 23.5% and 0% (p=0.03). Conclusion: When the ankles are affected and edema is observed, RS3PE is more likely than seronegative RA. RS3PE had higher levels of CRP, ESR, and LDH. The proportion of anemia was higher in RS3PE. The proportions of infection requiring hospitalization and the history of malignancy were higher in RS3PE. References: [1]McCarty DJ, O'Duffy JD et al. Remitting Seronegative Symmetrical Synovitis with Pitting Edema (RS3PE Syndrome). JAMA 1985; 254: 2763–2767. DOI:10.1001/jama.1985.03360190069027 Disclosure of Interests: Misako Higashida-Konishi: None declared, Keisuke Izumi Grant/research support from: Asahi Kasei Pharma, Takeda Pharmaceutical Co., Ltd., Speakers bureau: Asahi Kasei Pharma Corp, Astellas Pharma Inc., Bristol Myers Squibb, Chugai Pharmaceutical Co., Ltd., Eli Lilly Japan K.K., Mitsubishi Tanabe Pharma Co., Satoshi Hama: None declared, Yutaro Hayashi: None declared, Yutaka Okano: None declared, Hisaji Oshima: None declared